Impact and correlates of sub-optimal social support among patients in HIV care. Issue 9 (2nd September 2021) - Fredericksen, R. J.; Gibbons, L. E.; Fitzsimmons, E.; Nance, R. M.; Schafer, K. R.; Batey, D. S.; Loo, S.; Dougherty, S.; Mathews, W. C.; Christopoulos, K.; Mayer, K. H.; Mugavero, M. J.; et al.
ABSTRACT: Social support (SS) predicts health outcomes among patients living with HIV. We administered a brief, validated measure of SS, the Multifactoral Assessment of Perceived Social Support, within a patient-reported outcomes assessment of health domains in HIV care at 4 U.S. clinics in English and Spanish ( n = 708). In univariate analysis, low SS was associated with poorer engagement in care, antiretroviral adherence, and health-related quality of life; current methamphetamine/crystal use, depression, anxiety, and HIV stigma (all p < 0.001); any use of either methamphetamines/crystal, illicit opioids, or cocaine/crack ( p = 0.001), current marijuana use ( p = 0.012), nicotine use ( p = 0.005), and concern for sexually transmitted infection exposure ( p = 0.001). High SS was associated with undetectable viral load ( p = 0.031). Multivariate analyses found low SS independently associated with depression (risk ratio (RR) 3.72, 95% CI 2.93–4.72), lower adherence (RR 0.76, 95% CI 0.64–0.89), poor engagement in care (RR 2.05, 95% CI 1.44–2.96), and having more symptoms (RR 2.29, 95% CI 1.92–2.75). Medium SS was independently associated with depression (RR 2.59, 95% CI 2.00–3.36), poor engagement in care (RR 1.62, 95% CI 1.15–2.29) and having more symptoms (RR 1.75, 95% CI 1.44–2.13). SS assessment may help identify patients at risk for these outcomes.